Unaccompanied homeless youth have extremely poor diet quality and nutritional status - Hatsu, Irene (Int J Adolesc Youth, 2018)
A lack of in-depth assessment of the nutritional status of homeless youth precludes interventions that achieve nutritional adequacy. We enrolled 118 unaccompanied homeless youth to obtain sociodemographic and health data along with dietary, anthropometric, biochemical, and clinical assessments. As a reference, homeless youth data were compared to a convenience sample of 145 college students. Obesity was prevalent among homeless youth than among college students (29% vs. 8% respectively (CI: 11.2, 29.9). Among homeless youth, 74% of females versus 41% of males were overweight/obese (CI: 14.9, 51.2). Homeless youth also had poor diet quality (44.37 (SD: 12.64)). Over 70% of homeless youth had inadequate intakes of vitamins A, C, D(3) and E, as well as calcium and magnesium. Our findings show increased weight, adiposity, and suboptimal intakes of essential nutrients among unaccompanied homeless youth. Further studies are needed to inform evidence-based nutrition interventions that will aid in improving their nutritional health.